Serum pentraxin 3 in relation to clinical and nailfold capillaroscopy findings in patients with systemic sclerosis - Wafaa Soliman; Amira A. Moharram; Aya Safar (Egyptian Rheumatology and Rehabilitation)
Abstract Background Systemic sclerosis (SSc) is a long-standing autoimmune disease identified by vascular and fibrotic changes related to injury of endothelium. Pentraxin (PTX3) has important role in innate immune and autoimmune processes. Recently, it has been implicated in microvascular alterations in various diseases. Nailfold capillaroscopy (NFC) is a noninvasive technique used to study microvasculature. The aim of this current research is to demonstrate the relationship between serum PTX3 and clinical and NFC findings in patients with SSc. Results Patients’ serum levels of PTX3 were raised compared to healthy controls (P < 0.001). There was a positive correlation between PXT3 serum levels and serum creatinine, pulmonary artery pressure (PAP), and nailfold capillary loop diameter (r = 0.926, 0.947, 0.986, and P < 0.001, respectively). However, serum PXT3 levels were negatively correlated with nailfold capillary density (r = − 0.927 and P < 0.001). SSc patients experiencing digital ulcers had considerably elevated PTX3 serum levels than SSc patients not experiencing digital ulcers (P < 0.001). However, PTX3 serum level, modified Rodnan skin score, and PAP were not shown to be correlated. Conclusion Serum PTX3 level was associated with high serum creatinine, high PAP, larger nailfold capillary loop diameter, and less density of nailfold capillary in SSc patients. PTX3 might be an indicator of vascular involvement in SSc patients.